2018
DOI: 10.3892/ijo.2018.4473
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced antitumour response of pimozide combined with the IDO inhibitor L‑MT in melanoma

Abstract: Melanoma is one of the most fatal and therapy-resistant types of cancer; therefore, identifying novel therapeutic candidates to improve patient survival is an ongoing effort. Previous studies have revealed that pimozide is not sufficient to treat melanoma; therefore, enhancing the treatment is necessary. Indoleamine 2, 3-dioxygenase (IDO) is an immunosuppressive, intracellular rate-limiting enzyme, which contributes to immune tolerance in various tumours, including melanoma, and inhibition of IDO may be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 63 publications
1
30
1
Order By: Relevance
“…Additionally, Pimozide has showed an anticancer effect on other types of cancer: melanoma, CNS tumours, osteosarcoma, neuroblastoma, myeloproliferative neoplasms, breast, lung, prostate, ovarian, colorectal, pancreatic and hepatocellular carcinoma . Although, patients with mental disorders such as schizophrenia are less likely to develop cancer than the general population, there are yet no reports about the cancer incidence specifically in Pimozide users.…”
Section: Pimozidementioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, Pimozide has showed an anticancer effect on other types of cancer: melanoma, CNS tumours, osteosarcoma, neuroblastoma, myeloproliferative neoplasms, breast, lung, prostate, ovarian, colorectal, pancreatic and hepatocellular carcinoma . Although, patients with mental disorders such as schizophrenia are less likely to develop cancer than the general population, there are yet no reports about the cancer incidence specifically in Pimozide users.…”
Section: Pimozidementioning
confidence: 99%
“…Additionally, Krummel, Neifeld and Taub investigated the effects of this drug in murine melanomas and observed inhibition of 50% of the C‐leucine and H‐TdR incorporation without loss in cell viability or cell counting, which indicates proliferative activity in melanoma cells decreased. Jia et al observed antitumour activity of Pimozide in vitro using B16 melanoma cell line, and investigated its effect combined with L‐methyl‐tryptophan (L‐MT) in vivo . The author's results demonstrated that Pimozide is able to regulate the proliferation, apoptosis and migration.…”
Section: Pimozide As a Potential Anticancer Agentmentioning
confidence: 99%
See 3 more Smart Citations